TRANSLATIONS OF POEMS FROM MORPO. - Beduya, Jose Perez; Popa, Allan (Kritika Kultura)
The article offers author's insights on translations of poems from the book of "Morpo," by Allan Popa including the information about the translator Jose Perez Beduya. Highlights of the information are translation of poems based on its morpheme, root word and the preservation of morphemic repetition. According to the author, the process of translation does not only focus to literal meaning instead on the manipulation of the words.